Caracterización de la manteca de cacao de tres variedades trinitario (CCN-51), nacional (EET-103) y forastero (IMC-67), Quevedo – Ecuador - Lucero Álvarez, Mariela Gissela (2015)
This investigation was carried out in the Laboratory of Bromatology of the State Technical University of Quevedo. The objective was to characterize physical-chemistry and sensorially the shortening of cocoa of three clones, CCN-51, EET-103 and IMC-67, of the experimental Property "it Dams It", and to elaborate white chocolate with them. A Design was applied Totally at random with 7 repetitions. The variables measures were pH, Acidity, Ashy and Energy. It was carried out the profile cromatográfico of the sour Palmítico, esteárico, Oleico and linoleico. The main characteristics were evaluated: Scent, Color and Texture of the shortening of cocoa, and a test of acceptance for the white chocolate. As for pH the T2 (EET-103) it had a superior value with 6.29, but T1 (CCN-51) and T3 (IMC-67) with 0.88% they presented a bigger acidity percentage. The biggest content of ashy T1 presented it (CCN-51) with 0.67%, of the energy expressed as cal/100gr T2 (EET-103) it had 903.31cal/100gr. The biggest percentage of sour palmitic was in the T2 (EET-103) with 29.00%, and in sour estearic, T3 (IMC-67) it overcomes to the other treatments with 37.23%.........